Equitable access to COVID-19 related health technologies: A global priority - Zeleke Temesgen Boru (South Centre, 2020)
Since COVID-19 was first identified, infections from the virus and the death toll have spiked abysmally. The pandemic has also paralyzed the economies (particularly, global trade, tourism and transport) of many countries. The dire social and psychological ramifications associated with the pandemic are also immense. The threat posed by COVID-19 on global health and the economic downturn resulting thereof necessitates the development of health technologies (such as medicines and vaccines). A global effort to invent new health technologies or the likely application of existing technologies is also underway since the outbreak of the pandemic. Even though the race to develop these technologies can be hailed as a pivotal undertaking, the development of health technologies alone may not expedite equitable access to the outcome of such development. Particularly, the lack of access to health technologies may befall if the conventional model of health technology pricing, which is derived from monopoly rights created by IP protection, is set. However, legal as well as policy tools can be used to overcome such hurdles and ensure global access to health technologies. In this sense, this paper discusses plausible legal and policy options that can help to accelerate access to health technologies targeting COVID-19.
Keywords: 300; Access to Medicines; Affordable Medicines; Coronavirus; Costa Rica; COVID-19; Diagnostics; Doha Declaration on the TRIPS Agreement and Public Health; Economic Crisis; Flexibilities; Global Health; Health; Health Technologies; Intellectual Property; Medicines Patent Pool (MPP); Pandemic; Patent; Patent Pool; Public Health; Research and Development (R&D); TRIPS; United Nations (UN); Vaccines; World Trade Organization (WTO); WTO